Current Approaches to Medieval Historiography - Lake, Justin (History compass, 2015)
In recent decades a variety of approaches have been adopted to wring as much meaning as possible out of medieval chronicles and narrative histories. Moving past the use of these texts merely as source material to reconstruct the history of the Middle Ages, scholars have begun to focus to an increasing extent on topics such as authorial intention, social and political function, audience, and textual transmission. This essay charts the development of new approaches to medieval historiography, focusing on: 1) the analysis of fictional elements in history; 2) the relationship between politics and history; and 3) the return to manuscripts as primary sites of historical communication.